Hoboken, N.J., Ordinances ch. 22, §§ 246-47 (1901) - (:unkn) unknown (My University, 1901)
Concerning the Manufacture, Storage, Transportation, and Sale of Powder, Nitro-glycerine, etc.: No person shall manufacture, have, keep or give away any gunpowder, blasting powder, gun cotton, nitro-glycerine or dualin within the limits of the City of Hoboken, except in quantities limited in the manner and upon the conditions herein provided and under such regulations in special cases as the Board of Fire Commissioners shall prescribe.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER